EDUCATIONAL TOURISM OF LOCAL WISDOM PRODUCTS IN THAILAND - Fatimah, Siska Ernawati; Komara , Acep; Srisuk, Prattana; Saha, Sanchita; Rahmatika, Dien Noviany (Transpublika Publisher, 2024)
Management of local wisdom-based tourism products, development and packaging of globally competitive local products can be packaged through educational tourism. Educational Tourism is an effort to introduce local wisdom products of a country. One of Thailand's local wisdom products is traditional pottery. However, the existence of pottery in the era of modernization began to be less attractive to the younger generation. This international service was carried out with the aim of recognizing local culture and local wisdom products and participating in painting traditional Thai pottery. This activity is a community service activity that collaborates between the Faculty of Economics and Business of Swadaya Gunung Jati University Indonesia, Panca Sakti Tegal University Indonesia, Thai Globa Businnes Administration Technological College Thailand (TGBC Thailand), Suan Dusit University and Eastern Instutite for Integrated Learning in Management University India. Community service activities were carried out in Nong Nooch Thailand, with a total of 30 participants consisting of 10 students and 20 lecturers. Through this international service, it fosters a sense of love and preservation of cultural heritage and local wisdom products of a country.